2013
DOI: 10.1101/gr.161638.113
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient CRISPR/Cas9-mediated knock-in in zebrafish by homology-independent DNA repair

Abstract: Sequence-specific nucleases like TALENs and the CRISPR/Cas9 system have greatly expanded the genome editing possibilities in model organisms such as zebrafish. Both systems have recently been used to create knock-out alleles with great efficiency, and TALENs have also been successfully employed in knock-in of DNA cassettes at defined loci via homologous recombination (HR). Here we report CRISPR/Cas9-mediated knock-in of DNA cassettes into the zebrafish genome at a very high rate by homology-independent double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
516
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(527 citation statements)
references
References 47 publications
11
516
0
Order By: Relevance
“…Pilot work shown here and elsewhere also demonstrates that targeted insertions are possible as well, thus promising even further developments on the near horizon such as protein tagging, reporter constructs, and tissue-specific expression constructs. Right now the main challenge with knockin strategies is the relatively low efficiency rate, although newer technologies such as NHEJ mediated knockin (Auer et al 2014) promise to dramatically improve this. Perhaps the most exciting thing about CRISPR-associated genome editing approaches, though, is the straightforward portability of the technology between species.…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pilot work shown here and elsewhere also demonstrates that targeted insertions are possible as well, thus promising even further developments on the near horizon such as protein tagging, reporter constructs, and tissue-specific expression constructs. Right now the main challenge with knockin strategies is the relatively low efficiency rate, although newer technologies such as NHEJ mediated knockin (Auer et al 2014) promise to dramatically improve this. Perhaps the most exciting thing about CRISPR-associated genome editing approaches, though, is the straightforward portability of the technology between species.…”
Section: Future Prospectsmentioning
confidence: 99%
“…It has been shown that knocking out factors in the NHEJ pathway can enhance the HDR pathway and increase gene targeting efficiency in Bombyx (Ma et al 2014;Zhu et al 2015). Some Cas9-mediated homology-independent knockin approaches have shown higher efficiency rates in zebrafish (Auer et al 2014) and human cell lines (He et al 2016), suggesting NHEJ repair may provide an alternate strategy to improve incorporation of donor DNA in Lepidoptera.…”
Section: Experimental Designmentioning
confidence: 99%
“…Recently, site-specific integration has been achieved in model fish using PhiC31 integrase or genome-editing technology [47][48][49], which would avoid nontarget effects that usually occur in fish with randomly integrated transgenes. So far, however, no ideal integration sites, like ROSA26 in mice and humans, have been found in fish.…”
Section: Discussionmentioning
confidence: 99%
“…The crRNA and Cas9 protein form a complex, with the crRNA targeting a specific DNA sequence and the Cas9 protein catalyzing a double-strand break at the target site (Auer et al 2014). The ease and relative low cost of CRISPR tools have made editing of the zebrafish genome accessible to many laboratories.…”
Section: Genome Editing With Targeted Nucleasesmentioning
confidence: 99%